Key Indicators Socio-Economic Development of Marine Capture Fisheries - Mintaroem, Karjadi; Achmadi, Achmadi (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2014)
In this study, we developed several socio-economic indicators to be combined with biological and ecological indicators, which will be used to conduct an assessment/evaluation of ecosystem-based fisheries management fisheries. Socio-economic indicators that we developed consists of five socio-economic criteria which is considered as an important attribute of the process in a changing socio-economic structure. The fifth indicator is; production economics, business conditions, income levels, market conditions, and the level of employment. In establishing key indicators above, we first create a reference point for the evaluation of the indicators comprising, reference points, targets and limit reference points established through comparisons with other industries or other fish. So from the results penetapatan reference point, this study will apply the indicators that have been developed on marine fisheries catch in Lamongan district, so that the final results of this study will show how the management of marine fisheries in Lamongan we can discuss together.